2019
DOI: 10.1186/s13148-019-0719-9
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of SEPT9 as a potential biomarker for early detection of cervical cancer and its overexpression predicts radioresistance

Abstract: Background Cervical cancer screening by combined cytology and HPV test has reduced the incidence of cervical cancer, but cytological screening lacks a higher sensitivity while HPV testing possesses a lower specificity. Most patients with invasive cervical cancer are treated with radiotherapy. However, insensitivity to radiotherapy leads to poor efficacy. Methods Illumina Methylation EPIC 850k Beadchip was used for genomic screening. We detected methylation of SEPT9 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 51 publications
6
53
0
Order By: Relevance
“…In our pilot study, we also found Septin9 transcript isoform v2 was highly methylated in cervical cancer tissues, whereas no methylation in cervicitis controls. We further confirmed that in cervical scrapings, increases in Septin9 methylation were significantly correlated with greater severity of cervical lesions, which was consistent with Jiao's recent report [20]. Strangely, approximately 15% Septin9 methylation were detected in the no-CIN lesion group of scrapings, while no Septin9 methylation was detected in fresh cervicitis tissue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our pilot study, we also found Septin9 transcript isoform v2 was highly methylated in cervical cancer tissues, whereas no methylation in cervicitis controls. We further confirmed that in cervical scrapings, increases in Septin9 methylation were significantly correlated with greater severity of cervical lesions, which was consistent with Jiao's recent report [20]. Strangely, approximately 15% Septin9 methylation were detected in the no-CIN lesion group of scrapings, while no Septin9 methylation was detected in fresh cervicitis tissue.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Connolly et al proved that methylated Septin9-v3 was associated with the occurrence of breast cancer [15], and other evidences showed Septin9-v2 also to be a novel biomarker for the detection of breast cancer [26]. A very recent study found that Septin9 was hypermethylated in cervical cancer tissues compared to the normal controls, with satisfatory sensitivity and specificity [20]. However, the feasibility of detecting Septin9 methylation in cervical scrapings has not yet been carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium (90 μL) and CCK-8 (10 μL) were subsequently added to each well and incubated for 2 h at 37°C. The optical density (OD value) of the cells was measured by a microplate reader (Model 3550 Microplate Reader, Bio-Rad Laboratories, Inc., Hercules, CA, USA) at a wavelength of 570 nm [25]. All experiments were performed in triplicate.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…3,4 Therefore, improving our understanding of the underlying cellular basis of CC development is critical for improving CC prevention and treatment. In recent decades, numerous factors, including high-risk human papillomavirus (HPV) infection, 5 immune system disorders, 6 aberrant DNA methylation, 7 and noncoding RNA deregulation, have been found to be involved in the development and progression of CC.…”
Section: Introductionmentioning
confidence: 99%